Quality assurance practices of internal examinations in selected Eswatini primary schools - Tshabalala, Goodness; Schlebusch, Gawie; Makola, Solomon (Educational Challenges, 2025)
Purpose/Aim: Internal examinations are essential for formative assessment, offering valuable insights into learner progress and informing teaching strategies. However, current quality assurance practices in these examinations are prone to various shortcomings. These flaws can significantly affect the reliability and fairness of assessments, potentially resulting in inaccurate evaluations of learner achievement. A key concern is identifying the challenges and limitations that undermine quality assurance in internal examinations within Eswatini’s primary schools. By highlighting these issues, this study aims to contribute to improvements that uphold the integrity and effectiveness of this crucial assessment tool. Methodology: This qualitative case study embedded within the interpretative paradigm enabled the researchers to gain an in-depth understanding of how quality is assured in internal examinations in primary schools. Data was generated from five conveniently selected schools, where two teachers from each school participated in the study by completing an open-ended questionnaire. Five principals from the selected schools were part of the study by participating in semi-structured interviews. Document analysis also formed part of the data-generation process: in each school a sample of examination papers and marked examination scripts were reviewed to assess quality assurance. Results: The findings revealed that maintaining the quality and integrity of internal examinations in Eswatini’s primary schools is still a serious concern. Identified problems affecting quality assurance in internal examinations were fairness, reliability, validity, restricted resources, a lack of second opinions on produced examination papers, insufficient uniformity, and inadequate examination supervision. Conclusions: Based on the findings the study recommends regular implementation of training programs specifically tailored to equip teachers and principals with the necessary skills and knowledge to manage school-based assessments. The study further suggests that a policy should be put in place to serve as a guide in the preparation, monitoring, and supervision of internal examinations.